Critical reasoning and philosophy a concise guide to reading, evaluating, and writing philosophical works - Holowchak, Mark Andrew 1958- (Rowman & Littlefield, 2004)
For use in introductory philosophy courses, this book teaches students techniques for critical thinking, reading and writing. Includes sections on how to organize papers, avoid common mistakes in writing, and to present arguments.